Effects of diclofenac sodium on the hippocampus of rats with acute subdural hematoma: histological, stereological, and molecular approach - Türkmen, Aysın Pınar; Kaplan, Suleyman; Aksoy, Abdurrahman; Altunkaynak, Berrin Zuhal; Yurt, Kıymet Kübra; Elibol, Ebru; Çokluk, Cengiz; Onger, Mehmet Emin (Folia Neuropathologica, 2016)
This study was aimed at evaluating the potential effects of acute subdural hematoma (ASDH) and diclofenac sodium (DS) therapy following ASDH on the rat hippocampus. Twenty-four male Sprague Dawley rats were used and divided into four groups. 0.1 ml of non-heparinized autologous blood from the tail vein of the animals in the non-treatment group (NTG) and treatment group (TG) was injected into the subdural space. The TG received intramuscular diclofenac sodium at a 15 mg/kg dose daily from the postoperative second hour to the seventh day after the operation. The control group (CG) and sham group (SG) were used for control and sham operations, respectively. On the postoperative eighth day, all animals were sacrificed, and the hippocampi of all animals were stereologically and histologically evaluated. Also blood samples of the animals were biochemically analyzed. As a result of the study, the mean number of neurons in CA1, CA2, and CA3 regions of the hippocampus and the total number of neurons were decreased in the hippocampus samples of the NTG and especially the TG subjects. When comparing the second blood samples, there was no difference between the levels of adrenaline and serotonin among the groups. However, after the operation, noradrenalin levels in the treatment group were found to be higher than those of the sham and control groups (p < 0.05). In the NTG and TG, histopathological findings were observed such as Nissl condensation as well as completely dead and indistinguishable neurons with abnormally shaped, shrunken cytoplasm and nuclei. Also necrotic areas on the specimens of the TG were seen. In immunohistochemical sections, c-FOS positivity was decreased in the NTG and especially the TG. Otherwise, PGC-1 positive cells were increased in the NTG and especially the TG. In this study, it was shown for the first time by means of stereological techniques that using DS after ASDH caused a decrease in the number of hippocampal neurons (CA1, CA2, and CA3 regions).